Food falls in the deep northwestern Weddell Sea - Stauffer, Julian B.; Purser, Autun; Griffiths, Huw J.; Smith, Craig R.; Hoving, Henk-Jan T. (Frontiers in Marine Science, 2022)
When pelagic organisms die and fall onto the deep-sea floor they create food falls, i.e., parcels of organic enrichment that subsidize deep benthic scavenging communities. The diversity and quantities of food falls remain unstudied for many ocean regions since they are stochastically deposited and rapidly scavenged. The Southern Ocean habitat supports large populations of megafauna but few food falls have been documented. To investigate the diversity and quantity of food falls in the northwestern Weddell Sea, we analyzed 8476 images from the deep seafloor that were captured during the expedition PS118 on RV Polarstern in 2019 by the camera system OFOBS (Ocean Floor Observation and Bathymetry System). OFOBS was towed 1.5 m above the seafloor along five transects (400 to 2200 m seafloor depth) east of the Antarctic Peninsula. We observed the carcasses of one baleen whale, one penguin, and four fish at depths of 647 m, 613 m, 647 m, 2136 m, 2165 m, and 2112 m, respectively, as well as associated scavenging fauna. To the best of our knowledge, we describe here the first in situ observations of deep-sea food falls for penguins and fish in the Southern Ocean. While the whale carcass seemed in an intermediate successional stage, both the penguin and the fish were likely recently deposited and three of the fish potentially resulted from fishery discards. Our relatively small data set suggests that a diverse array of food falls provide nutrients to the slopes of the Powell Basin.